Market Reaction to the Launch of Danantara: An Event Study of State-Owned and Non-State-Owned Companies in Indonesia - Dian Purnamasari, Gisilowati (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
The analysis compares the stock performance of state-owned enterprises (SOEs) and non-state-owned enterprises (non-SOEs) over a 70-day period before and a 10-day period after the event. Whereas the investors' immediate reaction is captured post-event, the pre-event period will help capture the possible pointer of the market anticipation. In this research, three key indicators will be utilized: abnormal return (AR), average abnormal return (AAR), and cumulative abnormal return (CAR). The three indicators are selected to give a better, precise, and systematic overview of the market's response to such crucial events as the launch of Danantara. The study findings indicated that the abnormal returns of State-Owned Enterprises (SOEs) were not marked in the entire study period of observation. Such a situation can be attributed to the nature of SOEs in long-term capital control. Also, the stable nature of such organizations makes them unlikely to be influenced by the short-term markets. It can also be seen that non-SOE stocks had statistically significant abnormal returns and that investors of these firms are probably sensitive to market opportunities and changes in the market, particularly where new government plans or policies, such as Danantara, are being implemented. In general, the findings indicate that SOEs are relatively insensitive to short-term market forces, but non-SOEs represent the predilections of market mood.